Systematic Consumption Risk in Currency Returns - Mathias Hoffmann; Rahel Suter (Center for Economic Studies and ifo Institute (CESifo), 2013)
We sort currencies by countries' consumption growth over the past four quarters. Currency portfolios of countries experiencing consumption booms have higher Sharpe ratios than those of countries going through a consumption-based recession. A carry strategy that goes short in countries that are in a consumption bust and goes long in countries with a consumption boom yields consistently positive excess returns. This excess return compensates for the risk of high negative returns in worldwide downturns. Our consumption carry factor prices the cross section of portfolios of currencies sorted on various characteristics (consumption, interest rates) and also does well on the cross section of bilateral currency movements. Eventually, a habit formation model allows to interpret these results: sorting currencies on past consumption growth is akin to sorting countries on risk aversion, and low (high) risk aversion currencies depreciate (appreciate) in times of global turmoil.
Keywords: E44; F31; F44; G12; G15; 330; foreign exchange; carry trade returns; consumption risk; asset pricing